Cuban Anarchism : the history of a movement - Fernández, Frank, 1944-; Bufe, Charles (Tucson : See Sharp Press, 2001)
This inspiring history of the Cuban anarchist movement is also a history of the Cuban labor movement. It covers both from their origins in the mid-19th century to the present, and ends with an enlightening analysis of the failure of the Castro dictatorship.
Introduction (by Chaz Bufe) -- A Note on Terminology -- A Note on the Translation -- Preface -- Index of Organizations & Acronyms -- Map of Cuba -- 1. Colonialism & Separatism (1865-1898) -- 2. Intervention & Republic (1899-1933) -- 3. Constitution & Revolution (1934-1958) -- 4. Castroism & Confrontation (1959-1961) -- 5. Exile & Eclipse (1962-2001) -- 6. Reality & Reflection -- Photo Insert -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Anarchism ; Cuba ; History; Anarchists ; Cuba ; History; Electronic books